THE RELATIONSHIP BETWEEN SOCIAL MEDIA AND DISORDERED EATING IN COLLEGE-AGED FEMALE GYMNASTS - J.C. Ausmus; Lindsey C. Blom; Sharon Bowman; Jean-Charles Lebeau (University of Ljubljana Press (Založba Univerze v Ljubljani), 2021)
While the relationships between media and eating disorders and disordered eating patterns in college-aged women have been extensively studied (e.g., Bissel, 2004; Grabe & Hyde 2009; Harper & Tiggeman, 2008; Yamamiya, Cash, Melnyk, Posavac, & Posavac, 2005), fewer studies have been conducted with female athletes. More specifically, limited studies have focused on the relationship between social media and eating behaviors of athletes participating in aesthetic sporting events, even though the highest rates of disordered eating patterns occur in sports where female athletes are scored on judges' opinions (Hausenblas & Carron, 1999; Smolak, Murnen, & Ruble, 2000; Sundgot-Borgen, 1994), and where leanness, thinness, and aesthetic skills and aspects are emphasized (Byrne & McLean, 2002; DiBartolo & Shaffer, 2002). Thus, the current study sought to understand the links among college gymnasts' perceptions of body image, disordered eating behaviors, and perceptions of athletes' body images presented on social media. Furthermore, the study also explored how criticism presented on social media relates to disordered eating symptomatology. The study was conducted via an online survey system by 72 18-25-year-old females who were currently competing or recently competed in club or collegiate gymnastics. Results found significant correlations between the severity of critical comments about physical appearance, emotional reaction to criticism about physical appearance, and disordered eating behavior in instances where the comments were not made on social media, but no correlation was found between severity, emotional reaction, and disordered eating behaviors for comments made on social media.